Nitrogen waste metabolism as a locus of nitrergic co-transmission in the brain - Bedont, Joseph L. (Frontiers in Behavioral Neuroscience, 2025)
Nitrogen detoxification pathways in the central nervous system supply a range of neurotransmitters, ranging from long-appreciated examples like nitric oxide and agmatine, to emergent neurotransmitters including spermidine, spermine, and polyamine-derived GABA. This review summarizes specialized nitrogen detoxification pathways in the brain, and evidence supporting several of these pathways’ metabolites as co-transmitters in neurons and glia. Known functional roles of these nitrergic co-transmitters in learning, sleep, addiction, and other neurological disorders will be discussed to elucidate the adaptive value of nitrergic co-transmission, with a particular focus on nitrergic modulation of coincidence detection at NMDA receptors. Finally, this review sums up with a discussion of how nitrogen homeostasis in the brain serves as a coordinating locus for the control of these nitrergic neurotransmitters, and approaches for identifying bona fide co-transmitter effects of these metabolites in future work.